Chronic lung disease following neonatal extracorporeal membrane oxygenation: a single-center experience - Perez Ortiz, Alba; Glauner, Anna Katrin; Dittgen, Felix; Doniga, Thalia; Hetjens, Svetlana; Schaible, Thomas; Rafat, Neysan (Frontiers in Pediatrics, 2022)
ObjectiveTo assess the incidence and severity of chronic lung disease (CLD) after neonatal extracorporeal membrane oxygenation (ECMO) and to identify factors associated with its development.MethodsA retrospective observational study in a neonatal ECMO center was conducted. All neonates who received support with ECMO in our institution between January 2019 and October 2021 were included and their pulmonary outcome was investigated.ResultsA total of 91 patients [60 with congenital diaphragmatic hernia (CDH), 26 with meconium aspiration syndrome, and 5 with other diagnoses] were included in this study. Sixty-eight (75%) neonates survived. Fifty-two (76%) ECMO survivors developed CLD. There was no statistical difference between patients with and without CLD with regard to gender or gestational age. Patients with CLD had lower birth weight, were younger at the initiation of ECMO, and required longer ECMO runs. Patients with CDH developed CLD more often than infants with other underlying diseases (94 vs. 60%). Seventeen ECMO survivors (25%) developed severe CLD.ConclusionThe incidence of CLD after neonatal ECMO is substantial. Risk factors for its development include CDH as an underlying condition, the necessity for early initiation of ECMO, and the need for ECMO over 7 days.
Gesehen am 25.08.2022